Ralstonia chuxiongensis sp. nov., Ralstonia mojiangensis sp. nov., and Ralstonia soli sp. nov., isolated from tobacco fields, are three novel species in the family Burkholderiaceae - Lu, Can-Hua; Zhang, Ying-Ying; Jiang, Ning; Chen, Wei; Shao, Xiaoli; Zhao, Zhi-Ming; Lu, Wen-Lin; Hu, Xiaodong; Xi, Yi-Xuan; Zou, Si-Yuan; Wei, Qiu-Ju; Lin, Zhong-Long; et al. (Frontiers in Microbiology, 2023)
Eight Gram-negative, aerobic, motile with paired polar flagella and rod-shaped bacteria were isolated from six tobacco fields in Yunnan, PR China. 16S rRNA gene sequence analysis revealed that all the strains belonged to the genus Ralstonia. Among them, strain 22TCCZM03-6 had an identical 16S rRNA sequence to that of R. wenshanensis 56D2T, and the other strains were closely related to R. pickettii DSM 6297T (98.34–99.86%), R. wenshanensis 56D2T (98.70–99.64%), and R. insidiosa CCUG 46789T (97.34–98.56%). Genome sequencing yielded sizes ranging from 5.17 to 5.72 Mb, with overall G + C contents of 63.3–64.1%. Pairwise genome comparisons showed that strain 22TCCZM03-6 shared average nucleotide identity (ANI) and digital DNA–DNA hybridization (dDDH) values above the species cut-off with R. wenshanensis 56D2T, suggesting that strain 22TCCZM03-6 is a special strain of the R. wenshanensis. Five strains, including 21MJYT02-10T, 21LDWP02-16, 22TCJT01-1, 22TCCZM01-4, and 22TCJT01-2, had ANI values >95% and dDDH values >70% when compared with each other. These five strains had ANI values of 73.32–94.17% and dDDH of 22.0–55.20% with the type strains of the genus Ralstonia individually, supporting these five strains as a novel species in the genus Ralstonia. In addition, strains 21YRMH01-3T and 21MJYT02-11T represent two independent species. They both had ANI and dDDH values below the thresholds for species delineation when compared with the type species of the genus Ralstonia. In strains 21YRMH01-3T and 21MJYT02-10T, the main fatty acids were summed features 3, 8, and C16:0; however, strain 21MJYT02-11T contained C16:0, cyclo-C17:0, and summed features 3 as major fatty acids. The main polar lipids, including diphosphatidylglycerol, phosphatidylglycerol, and phosphatidylethanolamine, were identified from strains 21YRMH01-3T, 21MJYT02-10T, and 21MJYT02-11T. The ubiquinones Q-7 and Q-8 were also detected in these strains, with Q-8 being the predominant quinone. Based on the above data, we propose that the eight strains represent one known species and three novel species in the genus Ralstonia, for which the names Ralstonia chuxiongensis sp. nov., Ralstonia mojiangensis sp. nov., and Ralstonia soli sp. nov. are proposed. The type strains are 21YRMH01-3T (=GDMCC 1.3534T = JCM 35818T), 21MJYT02-10T (=GDMCC 1.3531T = JCM 35816T), and 21MJYT02-11T (=GDMCC 1.3532T = JCM 35817T), respectively.